Can information campaigns impact preferences toward vote selling? Theory and evidence from Kenya. Issue 3 (June 2020) - Erlich, Aaron
What factors shape citizens' willingness to engage in vote selling? This paper argues that providing voters with information about the detrimental effect of vote selling (public service predation) or telling them that their community members will look down on them if they engage in the practice (social sanctioning) can shape vote-selling attitudes in emerging democracies. Using a nationwide randomized survey experiment carried out between May and June of 2012 in Kenya, this study primes voters with theory-based informational messages for voters to test whether such messages can potentially curtail vote-selling attitudes. The paper finds that both public service predation and social sanctioning messages can reduce stated vote-selling preferences as much as legal campaigns that have been tested previously. The study has important implications for researchers and policy-makers because it suggests alternative methods to change vote-selling attitudes and even behavior in the short- to medium-term.